The effect of financial performance on the company’s zakat ability with company size as a moderating variable in islamic insurance companies for the period 2015-2023 - Rizky Alfahiz , Anang; Nurdin, Ade Ali; Nugraha, Muhamad Arif (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study analyzes the effect of financial performance on zakat capacity with company size as a moderating variable in Islamic insurance companies in Indonesia during 2015–2023. Financial performance is measured using ROA, CR, DER, and TATO, while company size is proxied by total asset growth. The research applies a quantitative approach using secondary data from annual reports of 8 Islamic insurance companies selected through purposive sampling. Data analysis is conducted using panel data regression with a random effect model. The results show that ROA, CR, DER, and TATO significantly and positively affect zakat capacity, both individually and collectively. However, company size does not moderate the relationship between TATO and zakat capacity. These findings highlight the importance of financial performance in influencing zakat payments, although company size does not always enhance this relationship